American Unitarian churches : architecture of a democratic religion - Borys, Ann Marie (University of Massachusetts Press, 2021)
"The Unitarian religious tradition was a product of the same eighteenth-century democratic ideals that fueled the American Revolution and informed the founding of the United States. Its liberal humanistic principles influenced institutions such as Harvard University and philosophical movements like Transcendentalism. Yet, its role in the history of American architecture is little known and studied. In American Unitarian Churches, Ann Marie Borys argues that the progressive values and identity of the Unitarian religion are intimately intertwined with ideals of American democracy and visibly expressed in the architecture of its churches. Over time, church architecture has continued to evolve in response to developments within the faith, and many contemporary projects are built to serve religious, practical, and civic functions simultaneously. Focusing primarily on churches of the nineteenth and twentieth centuries, including Frank Lloyd Wright's Unity Temple and Louis Kahn's First Unitarian Church, Borys explores building histories, biographies of leaders, and broader sociohistorical contexts. As this essential study makes clear, to examine Unitarianism through its churches is to see American architecture anew, and to find an authentic architectural expression of American democratic identity"--